McCain the myth of a maverick - Welch, Matt (Palgrave Macmillan, 2007)
John McCain is one of the most familiar, sympathetic, and overexposed figures in American politics, yet his concrete governing philosophy and actual track record have been left curiously unexamined, mostly because of the massive distractions in his official biography, but also because of his ingenious strategy of talking ad infinitum to each and every access-craving media person who happens by. The more he has spouted, the less journalists have bothered trying to see through the fog.